Effectiveness of glass as a substitute for cement and fine aggregate in concrete mix - Osman, Mohamad Hairi; Razali, Nurul Faraheka (Penerbit UTHM, 2017)
Construction field is a field that is wider than the other fields. The construction is becoming increasingly rapidly to meet the growing population. In the field of construction, concrete is an essential element to construct a building. Production of concrete leads to a reduction in natural resources as materials used in producing a concrete. For example of fine aggregate and cement. Furthermore, this problem gets attention from some parties in finding an alternative to reduce waste and maintained the natural resources to produce concrete using waste materials. Therefore, waste materials will be used in the concrete mix to reduce landfill and can reduce residual waste. Glass has high potential to be replaced as a cement-pozzolan [1]. Glass can be used in concrete as three kinds of elements include coarse aggregate, fine aggregate, and powder. Thus, the aim of this project is to replace glass as the replacement of cement and fine aggregate in concrete. In significant of this study, the issues regarding environmental can be reduced. Moreover, recycling waste will help to conserve the earth's natural resources, reduce landfill space and save energy and money [2]. Thus, this study will give an advantage to the various parties, particularly in the field of construction.